Innate-like T cells in liver disease - Yang, Albert Ying-Po; Wistuba-Hamprecht, Kilian; Greten, Tim F.; Ruf, Benjamin (Trends in immunology, 2024)
Mammalian innate-like T cells (ILTCs), including mucosal-associated invariant T (MAIT), natural killer T (NKT), and γδ T cells, are abundant tissue-resident lymphocytes that have recently emerged as orchestrators of hepatic inflammation, tissue repair, and immune homeostasis. This review explores the involvement of different ILTC subsets in liver diseases. We explore the mechanisms underlying the pro- and anti-inflammatory effector functions of ILTCs in a context-dependent manner. We highlight latest findings regarding the dynamic interplay between ILTC functional subsets and other immune and parenchymal cells which may inform candidate immunomodulatory strategies to achieve improved clinical outcomes in liver diseases. We present new insights into how distinct gene expression programs in hepatic ILTCs are induced, maintained, and reprogrammed in a context- and disease stage-dependent manner.
Online verfügbar: 14. Juni 2024, Artikelversion: 11. Juli 2024
Gesehen am 30.01.2025